A Study On Acceptance Of Advertisement In Mobile Device By Malaysian Customers - Asgari, Maryam (2009)
The purpose of this study, simple random sampling was a strategy that was used to select the sample by designing the questionaire in www.Gizmo.com and publish the questionaire's link among targets as mailed questionaire.